Low temperature limits for root growth in alpine species are set by cell differentiation. Issue 6 (19th October 2017) - Nagelmüller, Sebastian; Hiltbrunner, Erika; Körner, Christian
Abstract : This paper explores the causes of plant growth cessation at critically low temperatures in arctic-alpine environments. We grew four alpine plant species in thermostated soil cylinders in the field in the Swiss Alps, monitored root growth and studied root tip anatomy. Roots stopped growing at temperatures between 0.8 and 1.4 degree signC. Microscopic examinations of root tips revealed that rates of cell elongation and differentiation control length growth. Xylem lignification appears to be a co-limiting factor at growth-limiting low temperatures. Abstract: Plant growth in cold climates is not limited by carbon assimilation (source activity) but rather by reduced carbon investment into new tissues (sink limitation). It has been hypothesized that all cold-adapted plants face similar growth constraints at low temperature mainly associated with the formation of new tissues. To explore the thermal limitation of plant tissue formation, we studied root growth and anatomical root tissue characteristics in four cold-adapted alpine species ( Ranunculus glacialis, Rumex alpinus, Tussilago farfara, Poa alpina ), grown in thermostated soils with a vertical temperature gradient approaching 1 °C. Above-ground plant organs were exposed to typical alpine climate conditions (high solar radiation and cool nights) at 2440 m a.s.l. in the Swiss Alps to assure continuous source activity. Image-based measurements of root growth (root elongation rates at 12-h intervals, RERs) were combined with anatomical examinations in thermally constrained root tips as well as with a functional growth analysis of entire plants. Temperatures in the range 0.8 to 1.4 °C were denoted as critically low temperature thresholds for root formation across the four species. The RERs per 12 h revealed that roots kept extending at low rates at 0.7–1.2 °C but cell elongation and xylem lignification were clearly inhibited in the terminal zones of root tips. Roots exposed to temperatures between 1 and 5 °C showed strongly reduced elongation rates so that these roots contributed very little to the entire root system compared to control roots grown at 10 °C. Hardly any secondary roots were formed at temperatures below 5 °C and total root mass was substantially lower (74 % reduction in comparison to control), also the above-ground biomass was reduced by 23 %. Cell elongation and differentiation rather than cell division control length and shape of root cells at the low temperature limit of growth. Lignification of root xylem is clearly constrained at temperatures below 3 °C.